Preserving the Fast: Ethical Practices of the Early Muslim Salaf - Md Faruk Hossen (Penerbit Hellow Pustaka, 2026)
Fasting (ṣawm) in the month of Ramaḍān represents one of the most significant acts of worship in Islam and serves as a comprehensive system of moral and spiritual discipline. While many contemporary Muslims restrict fasting to abstinence from food and drink, classical Islamic teachings demonstrate that fasting encompasses the regulation of behavior, speech, and inner character. Early Muslim generations, known as the Salaf al-Ṣāliḥ (righteous predecessors), developed a distinctive methodology to safeguard the integrity of their fasts by avoiding sins, controlling the senses, and increasing devotion. This study analyzes Qur’ānic guidance, prophetic traditions, and early Islamic reports preserved in classical sources to examine how the Salaf preserved the ethical and spiritual dimensions of fasting. Using qualitative textual analysis, the research identifies practical measures adopted by them, including guarding the tongue, avoiding backbiting and falsehood, reducing social distractions, remaining in mosques, minimizing harm to others, and intensifying acts of worship. The findings reveal that fasting was understood as a holistic ethical system integrating both restraint and active devotion. The paper argues that reviving these practices can restore the transformative spirit of Ramaḍān and strengthen moral consciousness in contemporary Muslim societies.